Testimony : a novel / Anita Shreve. - Shreve, Anita. (Little, Brown, 2008)
At a New England boarding school, a sex scandal is about to break. Even more shocking than the sexual acts themselves is the fact that they were caught on videotape. A Pandora's box of revelations, the tape triggers a chorus of voices--those of the men, women, teenagers, and parents involved in the scandal--that details the ways in which lives can be derailed or destroyed in one foolish moment.